Antimicrobial and Immunomodulatory activities of Moringa peregrine- MINIREVIEW (Journal of Basic and Applied Research in Biomedicine, 2022)
Moringa peregrina is considered as miracle tree. Extracts as well as some isolated compounds of Moringa peregrine show valuable biological activities, such as antimicrobial, antiviral, anticancer, antioxidant, immunomodulatory. On the other hand, Moringa peregrina is used traditionally as home cleaning agent, fertilizer, foliar nutrient, green fertilizer, gum, honey- and sugar cane juice-clarifier, biopesticide. In this review, the natural distribution and the general features for Moringa peregrina were discussed and the antimicrobial and immunomodulatory activities of Moringa peregrine extract were described. This review might guide researchers to undertake further investigation regarding this species and to use it as a source of active compounds.